COGNITIVE BEHAVIOURAL THERAPY IN EDUCATIONAL SETTINGS: EMPOWERING STUDENTS TO OVERCOME CONCENTRATION CHALLENGES THROUGH INDIVIDUAL COUNSELING - Ainul Izzah; Rusmiyati; Anis Tri Yuliana (EDUCATIONE, 2025)
Learning concentration is a critical factor influencing students’ academic achievement, particularly for final-year Madrasah Aliyah (MA) students who face intense examination pressures and environmental distractions. Despite the prevalence of concentration problems, conventional school interventions often fail to address the underlying cognitive and behavioral barriers. This study aimed to examine the effectiveness of individualized Cognitive Behavioural Therapy (CBT)-based counseling in improving learning concentration among final-year MA students at MA Nurun Najah Sumberkima. Employing a qualitative case study design, data were collected through in-depth interviews, participant observation, and document analysis involving six students with documented concentration difficulties, supported by input from teachers and parents. The intervention consisted of six weekly CBT counseling sessions focusing on assessment, psychoeducation, cognitive restructuring, behavioral activation, and relapse prevention. Thematic analysis revealed substantial improvements in students’ focus, classroom engagement, time management, and academic performance, with average grades increasing by 10–15 points and greater consistency in task completion. The findings conclude that individualized CBT-based counseling is effective in alleviating anxiety, restructuring negative thinking, and fostering positive study habits in a culturally specific educational context. This research is beneficial for educators and school counselors, offering an empirically validated model for enhancing concentration and academic readiness. Future studies should explore the long-term impacts of individualized versus group-based CBT interventions across broader student populations.